Predictive nomogram for postoperative atrial fibrillation in locally advanced esophageal squamous carcinoma cell with neoadjuvant treatment - Fang, Meiqin; Chen, Mingduan; Du, Xiaoqiang; Chen, Shuchen (Frontiers in Surgery, 2023)
Background The neoadjuvant therapy following minimally invasive esophagectomy is recommended as the standard treatment for locally advanced esophageal squamous carcinoma cells (ESCC). Postoperative atrial fibrillation (POAF) after esophagectomy is common. We aimed to determine the risk factors and construct a nomogram model to predict the incidence of POAF among patients receiving neoadjuvant therapy. Methods We retrospectively included ESCC patients receiving neoadjuvant chemotherapy(nCT), neoadjuvant chemoradiotherapy(nCRT), or neoadjuvant immunochemotherapy(nICT) following minimally invasive esophagectomy(MIE) for analysis. Patients without a history of AF who did not have any AF before surgery developed new AF after surgery was defined as POAF. We applied LASSO regression analysis to avoid the collinearity of variables and screen the risk factors. Then, we applied the multivariate regression analysis to select independent risk factors and constructed a nomogram model to predict the POAF. We used the receiver operating characteristic (ROC) curve, calibration curve, and decision curve analysis (DCA) curve to evaluate the nomogram model. Results A total of 202 patients were included for analysis, with 35 patients receiving nCRT, 88 patients receiving nCT, and 79 patients receiving nICT. POAF occurred in 34 patients(16.83%). There was no significant difference in the distribution of neoadjuvant types between the POAF group and the no POAF group. There was a significant increase in postoperative hospital stay (P=0.04), hospital expenses(P=0.01), and comprehensive complication index (P<0.001). The LASSO analysis screened: blood loss, EF, FEV1, preoperation albumin (Alb), postoperation hemoglobin (Hb), preoperation Hb, hypertension, time to surgery, age, and left atrial (LA) diameter as risk factors. Further, preoperation Alb≦41.2g/L (P<0.001), preoperation Hb>149g/L (P=0.01), EF>67.61% (P=0.008), and LA diameter >32.9mm (P=0.03) were determined as independent risk factors of POAF in multivariate logistic analysis. The nomogram had an area under the curve (AUC) of 0.77. The Briser Score in the calibration curve was 0.12. The DCA confirmed good clinical value. Conclusions Preoperation Alb≦41.2g/L, LA diameter>32.9mm, preoperation Hb>149g/L, and EF>67.61% were determined as the risk factors for POAF among ESCC patients. A novel and valuable nomogram was constructed and validated to help clinicians evaluate the risk of POAF and take personalized treatment plans.